Novas formas de organização da produção canavieira na região de Ribeirão Preto/SP: qualificação profissional e o Programa Renovação - Salata, Rosemeire [UNESP] (2013)
This research is a reflection effort, in the light of the restructuring of production and accelerated introduction of technologies, guidelines about the business and labor around the qualification directed at workers cutting cane. We aim to establish connections and relationships between key recent modernization of this sector, whose primary dimension is based on the mechanization of cane harvesting, and their impacts on sugarcane workers regarding the professional qualification. We developed the survey based on the sugarcane region of Ribeirão Preto/SP, the country's most important, and focus our analysis on a form of professional qualification developed under the so called Programa Renovação. The observation carried sought to unveil the elements that characterize it as adequacy of technical and behavioral workforce arising from forms of management of labor employed by firms sugarcane before restructuring underway, and relate it to the political choices of the union movement before the political-economic context of the last decade